Dietary fat and cholesterol and risk of diabetes in older adults - Alqadheb, Ahmad; Alsalman, Noor; Noor Elahi, Alaa; Alobaidan, Mohammed; Shams, Sarah; Alharthi, Moeid; Banjar, Ghadeer; Alasiri, Reham; Yamani, Rzaz; Al-Rasheed, Rana (International Journal Of Community Medicine And Public Health, 2018)
Type 2 diabetes is a major global public health issue, and the rapid increase in prevalence over the past decades is expected to continue. The present analysis aimed to investigate the relation between egg consumption and type 2 diabetes risk in older adults. We conducted this meta-analysis using a comprehensive search of MEDLINE, PubMed, EMBASE, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials till 01 February 2018 for prospective observational studies that assessed the relationship of the dietary fat and cholesterol and risk of diabetes in older adults. We identified 15 prospective studies that could be included in the meta-analysis. When comparing the highest with the lowest category of egg intake, pooled multivariate RRs of incident diabetes mellitus were 1.25 (95% CI: 1.13, 1.44) using a fixed-effect model and 1.12 (95% CI: 1.01, 1.56) using a random-effect model. There was evidence for heterogeneity (I2=75.8%, p<0.001). Our meta-analysis shows no relation between infrequent egg consumption and diabetes mellitus risk but suggests a modest elevated risk of diabetes mellitus with ≥3 eggs/wk that is restricted to US studies.